Use of biotechnology as generator of resistance mechanism to water stress in the rosa productive chain (rosa indica l. var. classy) (2018)
Liquid humic substances are one of the biotechnological alternatives for organic agriculture, mainly those that are obtained from recyclable organic sources such as compost and vermicompost. Therefore, the main objective of this research was to evaluate the effect of biofertilization with Liplant on the growth, development and water relations of rose plants, exposed to water stress conditions. The experiment was carried out under semicontrolled conditions in the central area of the National Institute of Agricultural Sciences (INCA), San José de las Lajas, Mayabeque province. Used were the species Rosa indica L. var. Classy; applying a completely randomized design, where the factors studied were the sprinkling with the biostimulant Liplant 1/40 v.v., and the water stress condition, with 4 treatments, 2 with control and two with stress; alternating in each case the application or not of the Liplant. The substrate used was composed of leached red ferralitic soil, combined with cachaza in proportion 3:1 v.v. It was observed that the index evaluated were significantly affected by the pre-established drought conditions, clearly showing a decrease of the biomass in the aerial parts of the plant, being more remarkable in plants without application of Liplant. Sprinkling with Liplant 1/40 v.v., allowed to increase the production of biomass, both in good wáter catering and in conditions of water deficit. This reflects that the efficient use of biotechnology helps to mitigate, in the case of rose cultivation, the negative effects of climate change. Copyright © 2018, AIDIC Servizi S.r.l.